Crisis bargaining in the European Union: Formal rules or market pressure?. (March 2019) - Finke, Daniel; Bailer, Stefanie
To what extent did the European Monetary Union crisis alter the logic of European Union decision making? We analyze the relevance of asymmetric market pressures as compared to that of formal voting and agenda setting rules by applying three established bargaining models to the 'EMU Positions' data. Accounting for the interdependence between issues and agreements, we locate actors' positions on three reform dimensions, namely the level of fiscal discipline, transfer payments and institutionalization. We find that market pressure during the height of the Eurozone crisis was particularly relevant, and that debtor countries were weakened by their difficulty in refinancing their public debt. Our finding shows that formal rules determining agenda setting and veto rights remain relevant even in times of crisis.